Correlation Analysis between Grounding Resistance and Diurnal Variations of Upper Soil Resistivity during March 2010 in Balozhi, Latvia - Kizhlo, Marina; Kanbergs, Arvids; Kizhlo, Mihails (Electrical, Control and Communication Engineering, 2010)
The accurate measurement of soil resistivity and grounding system resistance is fundamental to electrical safety. However, geological and meteorological factors can have a considerable effect on the accuracy of conventional measurements and the validity of the measurement methods. This paper examines some aspects of grounding measurements and grounding system performance in the context of both geological and meteorological effects.We are reporting the results of grounding measurements using the 3-point method with ground resistivity tester type M416. The measurements were conducted during selected period from 2010 March 1 to March 31 in Balozhi, Latvia. We also noted that the resistivity of the upper layer significantly varied from a point to another, reflecting difference in water content in the upper soil layer due to local topography and other parameters.